Dimeric phosphorylation of glyoxalase I alters its symmetry and substrate binding mechanism: simulation studies. Issue 12 (14th July 2022) - Barber, Lisa Michelle; Hussain, Zakir; Thomas, Merlin; Hung, Andrew
Abstract: Glyoxalase I (GLO1) is a dimeric esterase of the glyoxalase system. Phosphorylation of the residue T106 has been found to inhibit GLO1 activity, and contribute to the onset of oxidative stress and cellular damage. This research uses multiple molecular dynamics simulations and automated docking of both GLO1 and dimerically phosphorylated GLO1 (p2-GLO1) to predict the initial structural differences induced by phosphorylation, and their interaction with the intermediate substrate Hemimercaptal. This research indicates that immediately following phosphorylation, GLO1 exhibits reduced sphericity, partly caused by outward splaying of the loop region surrounding T106. Phosphorylation induces enhanced concerted motions in the loop composed of residues immediately surrounding T106, which are correlated with motions at the active site pocket at the distant, opposite end of the dimer. These T106 region loop motions result in the distortion of the shape of the active site, and potentially alter its accessibility. Phosphorylation alters the manner in which GLO1 interacts with Hemimercaptal. For GLO1, Hemimercaptal is predicted to bind to T106, which we propose constitutes a novel, highly accessible 'capture site' responsible for initial contact with the substrate. In contrast, for p2-GLO1, Hemimercaptal is unable to bind favourably to (phosphorylated) position T106, suggesting that this proposed transient 'capture site' is abolished upon phosphorylation of GLO1. Hence, a novel physiological role is here proposed for the known essential GLO1 residue T106. These results may further contribute to understanding the inhibition mechanism of GLO1 upon phosphorylation. Communicated by Ramaswamy H. Sarma